2016
DOI: 10.1007/s00125-016-4121-2
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-related transcriptional signature is downregulated in adipocytes in obesity: a study of young healthy MZ twins

Abstract: The datasets analysed and generated during the current study are available in the figshare repository, https://dx.doi.org/10.6084/m9.figshare.3806286.v1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 51 publications
(69 reference statements)
5
54
0
2
Order By: Relevance
“…Table 1 summarizes the subjects’ anthropometric and clinical characteristics (2628). In brief, the heavier co-twins of the discordant pairs weighed on average 18 kg more, had 28% more total fat, 67% more subcutaneous fat, 200% more intra-abdominal fat, and 300% more liver fat than their leaner counterparts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 summarizes the subjects’ anthropometric and clinical characteristics (2628). In brief, the heavier co-twins of the discordant pairs weighed on average 18 kg more, had 28% more total fat, 67% more subcutaneous fat, 200% more intra-abdominal fat, and 300% more liver fat than their leaner counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…The study population has been described in our previous studies (2628). Briefly, the monozygotic (MZ) twin pairs (aged 22–36, 54% women) were identified through the national population registry of Finland from 10 population-based birth cohorts (FinnTwin12 and FinnTwin16); 26 pairs being discordant for BMI, within-pair difference (Δ) in BMI >3 kg/m 2 (mean Δweight 18 kg), and 14 pairs concordant for BMI (ΔBMI <3 kg/m 2 ) acting as their controls.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, subcutaneous fat cells taken from heavier versus leaner discordant twin donors show lower mitochondrial-encoded gene expression including the 12S rRNA gene 12. Whether this finding has any implications for muscle MOTS-c expression and release is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…When ROS production increases, the balance between oxidant and antioxidant factors is disturbed and oxidative stress occurs. 9 Proinflammatory adipokines and elevated levels of FFAs, in particular those released by visceral adipose tissue, cause IR and are pathogenic factors that can induce endothelial dysfunction in the earlier stages of obesity, which further deteriorates insulin signalling pathways in endothelial cells, thus leading to initiation of the atherosclerotic process. 2 Several studies have shown that an increase in ROS production in adipose tissue of experimental animal models of diabetes and obesity or in cultured adipocytes can cause altered synthesis and secretion of adipokines and promote cell senescence, IR and an inflammatory response.…”
Section: Introductionmentioning
confidence: 99%